David R. Blumenthal - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2014)
David R. Blumenthal is Jay and Leslie Cohen Professor of Judaic Studies at Emory University. He has contributed greatly to the growth of Jewish Studies, the place of Judaism in Religious Studies, interreligious dialogue, and the reframing of Judaism in light of the Holocaust, postmodernism, and poststructuralism. For Blumenthal, theology is an ongoing reflection about everything we believe and do in the context of the living tradition.